4(2x-7)=3(2x+1)

Simple and best practice solution for 4(2x-7)=3(2x+1) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4(2x-7)=3(2x+1) equation:


4(2x-7)=3(2x+1)

We simplify the equation to the form, which is simple to understand
4(2x-7)=3(2x+1)

Reorder the terms in parentheses
+(+8x-28)=3*(2x+1)

Remove unnecessary parentheses
+8x-28=+3+*(+2x+1+)

Reorder the terms in parentheses
+8x-28=+(+6x+3)

Remove unnecessary parentheses
+8x-28=+6x+3

We move all terms containing x to the left and all other terms to the right.
+8x-6x=+3+28

We simplify left and right side of the equation.
+2x=+31

We divide both sides of the equation by 2 to get x.
x=15.5

See similar equations:

| 40=2m+24 | | solvex-9y=17fory | | (5x-6)(3x+7)= | | n^2+32n+240=0 | | 4.2=n-1.6 | | 2(6x+2)= | | 8x-y-23=0 | | 36a^4+27a^3b= | | 8x+y+23=0 | | 15xy+25x+9y+15=0 | | 24x^2-20x=56 | | 11a^3b-2a^2b^4= | | ln(x)+ln(x-2)=ln(4x) | | 3x-20=-155 | | 4q^2+9q-9=0 | | 4x+7=22+7x | | 3(4x-1)+11=5x+22 | | 1=-11+12 | | 15y-7=0 | | (-2x^2+6x+1)-2(4x^2-3x+1)=0 | | 13x-8+3-2= | | 10x-8y-12+6y-15x+20-(3x+7)= | | t^2+64=0 | | -10-3x+7x=6 | | 3=-11+4 | | -10/a-0.5=2 | | (3y-7x+7)dx+(7y-3x+3)dy=0 | | 10x+8y-12+6y-15x+20= | | log[3](45)-log[3]x=log[3]9 | | 3(4x-1)+11=5x+23 | | 49k^2=-294-385k | | 10x-8y-12+6y-15x+20= |

Equations solver categories